Estimating the total energy costs of a brief 1-minute bout of heavy bag punching - Christopher Scott (Asociación Española de Ciencias del Deporte, 2019)
Introduction: We compared a one minute total energy cost estimate - aerobic and anaerobic, exercise and recovery - with published per minute exercise-only oxygen uptake measures for pugilistic exercise. Material and Methods:  Ten male subjects completed testing: 25.6 ± 3.5 years; ht 180.5 ± 8.0 cm; wt 80.7 ± 8.4 kg. The punching exercise (using wrapped hands and 16 oz. gloves) included: 6 rapid punches to a hanging heavyweight bag followed by a brief pause for a total of 16 sets; in all 96 punches were completed within 61.5 ± 5.3 sec of exercise. The protocol was repeated twice and an average net cost of the 2 trials was reported. Results and Discussion: Aerobic exercise costs were 33.1 kJ ± 5.5 (7.9 ± 1.3 kcal), anaerobic energy costs were 37.1 ± 8.9 kJ (8.9 ± 2.1 kcal), excess post-exercise oxygen consumption (EPOC) was 83.4 ± 15.8 kJ (19.9 ± 3.8 kcal) and total energy costs were 153.7 ± 20.1 kJ (36.7 ± 4.8 kcal). For brief intense pugilistic exercise, our total energy cost estimate was as much as 4.5-fold greater than previously published per minute exercise oxygen uptake rates. It is concluded that the steady state modeling of energy costs should not be judiciously applied to brief, intense, non-steady state, intermittent exercise.